Optimization of fuel cell switching control based on power following strategy in fuel cell hybrid electrical vehicle - Deng, Leipengyun; Mohd Radzi, Mohd Amran; Shafie, Suhaidi Bin; Hassan, Mohd Khair (Center of Biomass & Renewable Energy (CBIORE), 2025)
Fuel cell hybrid electric vehicles (FCHEVs), integrating fuel cell (FC) with batteries, have attracted significant research attention due to their emission-free operation, enhanced efficiency, and quick refuelling capabilities. Efficient energy management strategies (EMSs) are crucial in allocating energy between these sources and controlling power flow from FCs and batteries. The power following control (PFC) strategy has emerged as one of the most extensively utilized approaches in automotive applications owing to its superior real-time performance, ease of calculation, and straightforward design. This paper proposes a PFC-optimized strategy focused on improving FC durability and fuel economy by optimizing the switching control to fill the gap in frequent toggling of FC caused by traditional PFC strategy. The outcomes derived from the co-simulation conducted with AVL CRUISE and MATLAB/Simulink for developing complete FCHEV model and EMS model, respectively, indicate that under the China Light-duty Vehicle Test Cycle for Passenger Car (CLTC-P), the PFC-optimized strategy, in comparison to the traditional PFC strategy, reduces battery state of charge (SOC) fluctuations by 68.93% and decreases hydrogen consumption per 100 km by 2.71%. Meanwhile, this strategy is also proven effective in other operating conditions and reduces fuel cell switching times during operation. Therefore, the PFC-optimized strategy suggested in this study contributes to better performance in battery SOC, battery life, FC durability and fuel economy.